Enterocutaneous fistula formation thirty years after a femoral neck fracture fixation with lag screws: A case report. (March 2021) - Najjari, Khosrow; Gouravani, Mahdi; Hajebi, Reza; Zabihi Mahmoudabadi, Hossein; Rahimpour, Ehsan
Highlights: Despite improvements in surgical care, ECF's proper management remains challenging. ECF can occur even 30 years later after orthopedic procedures in the hip area. ECF care requires strict adherence to tenets like sepsis control and resuscitation. Abstract: Introduction and importance: As the population grows older, femoral neck fracture is becoming one of the prevalent cases in orthopedics, although this fracture can also happen in younger individuals following high energy traumas. Fixation with cancellous lag screws is one treatment option for femoral neck fractures, especially for young adults and relatively active older patients. Case presentation: In this case report, we describe a 52-year-old man referred with the formation of enterocutaneous fistula (ECF) in the surgery place for fixation of a femoral neck fracture 30 years prior to presentation. Clinical discussion: Interpretation of CT scan images as well as findings of the performed laparotomy suggested that fixation procedure with screws was probably the main culprit for penetration of ileum. Subsequently, the removal of screws enabled the fistula to reach the surface of skin, which presented with fecal drainage. To eliminate fistula, we performed right hemicolectomy and ileocolic anastomosis for the case. Conclusion: Since management of ECF remains among the most challenging problems for surgeons, this unique case report indicates the possibility for formation of such fistula following a fixation procedure in the hip joint area, even after thirty years and stresses on taking measures in order to prevent fistula formation caused by the prevalent procedures performed on the hip joint.